AI Sport Forecast Software - Cerezo Takahashi, Kiyomi (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
This article aims to explain the development of an application whose function is to predict the results of different sporting encounters. To do this an analysis of the influential factors, algorithms and technology implemented, will be carried out.
Keywords: bayesian network; data mining; IJIMAI